Targeting regulatory T cells by E7777 enhances CD8 T-cell–mediated anti-tumor activity and extends survival benefit of anti-PD-1 in solid tumor models - Mahdi, Haider S.; Woodall-Jappe, Mary; Singh, Preeti; Czuczman, Myron S. (Frontiers in Immunology, 2023)
Introduction: Regulatory T cell (Treg)-targeting cancer immunotherapy aims to transiently deplete Treg cells in the tumor microenvironment, without affecting effector T cells (Teff), thus both enhancing anti-tumor activity and avoiding autoimmunity. This study evaluated whether adding E7777 (a new formulation of denileukin diftitox [DD]) improved the efficacy of anti-PD-1 antibody therapy. DD is a recombinant protein containing the hydrophobic and catalytic portions of diphtheria toxin fused to full-length human IL-2. E7777 has the same amino acid sequence and brief circulatory half-life as DD, but with greater purity and potency.Methods: Subcutaneous syngeneic murine solid tumor models (colon cancer CT-26 and liver cancer H22) were used to evaluate safety, efficacy, and overall survival with E7777 and anti-PD-1 antibodies, each administered as monotherapy or in concurrent or sequential combination. In Experiment 1, treatments were compared to assess anti-tumor activity at various time points, with tumors excised and dissociated and tumor leukocytes characterized. In Experiment 2, tumor growth, response, and overall survival were characterized for 100 days following a 3-week treatment.Results: E7777 administered in combination with anti-PD-1 led to significantly increased antitumor activity and durable, extended overall survival compared to either treatment alone. In both tumor models, the Treg cell infiltration induced by anti-PD-1 treatment was counterbalanced by co-treatment with E7777, suggesting potential synergistic activity.Combination therapy showed the most favorable results. Treatment with E7777 was safe and well-tolerated.Discussion: Combined E7777 and anti-PD-1 therapy was well tolerated and more effective than monotherapy with either drug.